Analisis Persepsi Dampak Limbah Tambak Udang Terhadap Pendapatan Nelayan Skala Kecil Di Kecamatan Mallusetasi, Kabupaten Barru - Zulkarnaen, Adi; Yusuf, La Ode Muhammad Iksan; Nyompa, Achmad Husein (Torani Journal of Fisheries and Marine Science, 2025)
Small-scale fisheries play a strategic role in the blue economy and food security in coastal regions. In Mallusetasi District, fishers still rely on traditional and environmentally friendly fishing gear, yet they remain vulnerable to changes in coastal ecosystems, including shrimp farming activities. This study aims to analyze the perceptions of small-scale fishers regarding the impact of shrimp pond waste on their income. A total of 40 respondents were selected through purposive sampling, and data were analyzed using a Likert scale and Spearman correlation. The Likert scale analysis produced a total score of 552, indicating that fishers perceive a decline in catch volume and income due to waste discharge and expansion of shrimp farms. However, the Spearman correlation test revealed no statistically significant relationship between shrimp farming activities and the income of small-scale fishers. These findings indicate a discrepancy between environmental perceptions and actual economic conditions, suggesting that fishers are able to adapt and maintain their income through various coping strategies. Further investigation is required to better understand the socio-economic adaptation dynamics of small-scale fishers amid the pressures of coastal aquaculture activities.